Structure and stability of recombinant bovine odorant-binding protein: III. Peculiarities of the wild type bOBP unfolding in crowded milieu - Stepanenko, Olga V.; Roginskii, Denis O.; Stepanenko, Olesya V.; Kuznetsova, Irina M.; Uversky, Vladimir N.; Turoverov, Konstantin K. (PeerJ, 2016)
Contrary to the majority of the members of the lipocalin family, which are stable monomers with the specific OBP fold (a β-barrel consisting of a 8-stranded anti-parallel β-sheet followed by a short α-helical segment, a ninth β-strand, and a disordered C-terminal tail) and a conserved disulfide bond, bovine odorant-binding protein (bOBP) does not have such a disulfide bond and forms a domain-swapped dimer that involves crossing the α-helical region from each monomer over the β-barrel of the other monomer. Furthermore, although natural bOBP isolated from bovine tissues exists as a stable domain-swapped dimer, recombinant bOBP has decreased dimerization potential and therefore exists as a mixture of monomeric and dimeric variants. In this article, we investigated the effect model crowding agents of similar chemical nature but different molecular mass on conformational stability of the recombinant bOBP. These experiments were conducted in order to shed light on the potential influence of model crowded environment on the unfolding-refolding equilibrium. To this end, we looked at the influence of PEG-600, PEG-4000, and PEG-12000 in concentrations of 80, 150, and 300 mg/mL on the equilibrium unfolding and refolding transitions induced in the recombinant bOBP by guanidine hydrochloride. We are showing here that the effect of crowding agents on the structure and conformational stability of the recombinant bOBP depends on the size of the crowder, with the smaller crowding agents being more effective in the stabilization of the bOBP native dimeric state against the guanidine hydrochloride denaturing action. This effect of the crowding agents is concentration dependent, with the high concentrations of the agents being more effective.
Keywords: Odorant-binding protein; Macromolecular crowding; Disulfide bond; Ligand binding; Conformational stability; Domain swapping; Unfolding-refolding reaction